2016
DOI: 10.1039/c6fo00089d
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis and immunostimulatory activity of glycopeptides from Paecilomyces sinensis

Abstract: The parasitic fungus, Paecilomyces sinensis, is used to produce Cordyceps materials as a succedaneum of natural Cordyceps sinensis (C. sinensis) in China. In this work, a glycopeptide (CPS-II) was isolated and purified from Paecilomyces sinensis. The result of HPLC indicated that CPS-II was a glycopeptide. The estimated average molecular weight of CPS-II was 2 × 10(6) Da. FTIR, methylation, periodate oxidation, Smith degradation, (1)H NMR, (13)C NMR and CD were used for its structural analysis. The glycopeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Zhu et al also studied a polysaccharide from Paecilomyces sinensis (CPS). 39 Those results indicated that CPS was a kind of glycopeptide with an average molecular weight of 200 kDa and represented an a-pyran type. CPS-II mainly contained xylose, mannose, glucose, and galactose with a molar ratio of 3.7 : 12.2 : 33 : 48.…”
Section: Resultsmentioning
confidence: 97%
“…Zhu et al also studied a polysaccharide from Paecilomyces sinensis (CPS). 39 Those results indicated that CPS was a kind of glycopeptide with an average molecular weight of 200 kDa and represented an a-pyran type. CPS-II mainly contained xylose, mannose, glucose, and galactose with a molar ratio of 3.7 : 12.2 : 33 : 48.…”
Section: Resultsmentioning
confidence: 97%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15] Our previous work revealed the structural analysis of glycopeptides from Paecilomyces sinensis and demonstrated that they can activate the macrophage RAW 264.7 through enhanced proliferation and phagocytosis activity in vitro. 16 The aim of this study was to demonstrate immune responses induced by CTX in vivo. However, due to excessive exploitation and utilization, the resources of Cordyceps are greatly decreased and researchers are faced with the situation of a short supply.…”
Section: Introductionmentioning
confidence: 99%
“…e absorption band at 1651.64 cm − 1 (amide I band) and 1536.44 (amide II band) cm − 1 were important characteristic absorption bands of protein, which indicated C�O stretching vibration, C-N stretching vibration, and N-H stretching vibration, respectively. e three absorption bands at 1500-1300 cm − 1 were triggered by the bending vibration of C-H, and two absorption bands at 1026-1152 cm − 1 suggested the existence of pyranose [42]. Besides, α-type glycosidic linkage in the LML was revealed by the absorption band at 879.22 cm − 1 [43].…”
Section: Ft-ir Analysismentioning
confidence: 92%